Upaya Meningkatkan Minat Belajar Peserta Didik Dalam Pembelajaran Penjaskes Melalui Penerapan Metode Pembelajaran Demonstrasi Di Kelas V SDN 18 Lembah Melintang - Yusliana S.Pd (JURNAL MANAJEMEN PENDIDIKAN, 2016)
Abstract Based on the learning process of students in class V SDN 18 Valley Crossing in teaching PE found that the interest of students in learning PE is still very low. The purpose of this study is to describe and obtain information about the efforts to increase the interest of learners in learning PE through the application of learning methods in the classroom demonstration of SDN 18 Valley Crossing Barat.Penelitian Pasaman of this is a class action. The procedure in this research include planning, action, and reflection obeserVsi. The study consisted of two cycles of the four meetings. Subject of the study consisted of 25 students in class V SDN 18 Valley Crossing. Data were collected by using observation sheet. Data were analyzed using persentase.Berdasarkan research and discussion that has been presented in the previous chapter, it can be concluded that it can be concluded that the model pembelajaan demonstration can increase the interest of learners in the learning of PE at SDN 18 Valley Crossing. Interests of learners from the first cycle to the second cycle. Interest of learners in the first cycle was 70.66 (enough) increased to 81.66 (good) with an increase of 11.00.Keywords: Interest in Learning, Teaching PE, learning model demonstration